2020
DOI: 10.1002/jbmr.4203
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease–Induced Vascular Calcification Impairs Bone Metabolism

Abstract: An association between lower bone mineral density (BMD) and presence of vascular calcification (VC) has been reported in several studies. Chronic kidney disease (CKD) causes detrimental disturbances in the mineral balance, bone turnover, and development of severe VC. Our group has previously demonstrated expression of Wnt inhibitors in calcified arteries of CKD rats. Therefore, we hypothesized that the CKD‐induced VC via this pathway signals to bone and induces bone loss. To address this novel hypothesis, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 61 publications
(94 reference statements)
3
41
0
Order By: Relevance
“…The gene analysis also showed a specific upregulation of the gene Sost, coding for the canonical Wnt inhibitor sclerostin, and downregulation of Wnt target genes. These novel results indicated not only that vascular calcification inhibited the anabolic Wnt pathway in bone, but it also affected several pathways representing a complex effect on bone metabolism, suggesting several factors secreted by the uremic calcified aorta (Figure 2) [80]. CKD rat was transplanted into a normal isogenic recipient.…”
Section: Calcified Vasculature Affects Bone Metabolismmentioning
confidence: 90%
See 2 more Smart Citations
“…The gene analysis also showed a specific upregulation of the gene Sost, coding for the canonical Wnt inhibitor sclerostin, and downregulation of Wnt target genes. These novel results indicated not only that vascular calcification inhibited the anabolic Wnt pathway in bone, but it also affected several pathways representing a complex effect on bone metabolism, suggesting several factors secreted by the uremic calcified aorta (Figure 2) [80]. CKD rat was transplanted into a normal isogenic recipient.…”
Section: Calcified Vasculature Affects Bone Metabolismmentioning
confidence: 90%
“…Recent research has identified several factors in the uremic condition to be involved in vascular disease and development of vascular calcification such as uremic toxins, reactive oxygen species, DNA damage, cell senescence, inflammation, loss of local and system calcification inhibitors, secondary calciprotein particles (CPPs), and kidney-derived injury factors [73][74][75][76]. Our group has studied the uremic vasculopathy in different experimental models of kidney disease [66,[77][78][79][80][81]. Recently, we have reviewed the role of the disturbed circadian clock in uremic vasculopathy and showed that it is a new important factor in the pathogenesis [81,82].…”
Section: Dramatic Changes In the Vasculature In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural and functional changes in the vasculature are observed early in CKD, including the altered expression of genes related to the developmental program and the contractility of VSMC, vascular stiffness and endothelial dysfunction [ 47 , 82 ]. Dedifferentiated VSMC are susceptible to osteoblastic transformation and in more advanced stages of CKD to the progressive accumulation of calcium crystals in the extracellular matrix and progressive calcification of neointima and lamina media of the vascular wall [ 82 , 83 ].…”
Section: The Vascular Circadian Clock Is Disrupted In Ckdmentioning
confidence: 99%
“…Vascular calcification (VC) is a useful marker of cardiovascular disease and several methods are available for the assessment of their presence and extension [1][2][3][4][5]. Although the pathogenesis of VC is not well established, several studies suggest that the prevalence of VC increases as renal function declines, likely due to the many metabolic abnormalities that characterize chronic kidney disease (CKD) [3,5,6]. Irrespective of the noxious mechanism responsible for VC deposition and progression, the data suggest that the risk of unfavorable outcome is higher for greater VC burden [2,5].…”
Section: Introductionmentioning
confidence: 99%